Compressed equilibrium in large repeated games of incomplete information - Ehud Kalai; Eran Shmaya (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2013)
Due to their many applications, large Bayesian games have been a subject of growing interest in game theory and related fields. But to a large extent, models (1) have been restricted to one-shot interaction, (2) are based on an assumption that player types are independent and (3) assume that the number of players is known. The current paper develops a general theory of Bayesian repeated large games that avoids some of these difficulties. To make the analysis more robust, it develops a concept of compressed equilibrium which is applicable to a general class of Bayesian repeated large anonymous games.
Keywords: C72; C73; 330; Anonymous games; Nash equilibrium; Repeated games; Large games; Bayesian equilibrium; Price taking; Rational expectations; Anonymous games; Nash equilibrium; Repeated games; Large games; Bayesian equilibrium; Price taking; Rational expectations